Rebuilding the Music Industry through Community: A Case Study of Bandcamp and Twitch during COVID - Léger, Devon (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Devon Léger is a music publicist (HearthPR) and music writer (Folk Alley, No Depression). In this piece, he describes how online music platforms Bandcamp and Twitch have supported musicians during the pandemic and provided new ways for artists to connect with fans, build community, and monetize their music.